Determinants and impact of role-related time use allocation on self-reported health among married men and women: a cross-national comparative study - Kenisha Russell Jonsson; Gustav Oberg; Florence Samkange-Zeeb; Nicholas Kofi Adjei (BMC, 2020)
Abstract Background Research on the effects of marriage on health maintains that there is a gender-specific gradient, with men deriving far greater benefits than women. One reason provided for this difference is the disproportionate amount of time spent by women on housework and childcare. However, this hypothesis has yet to be explicitly tested for these role-related time use activities. This study provides empirical evidence on the association between role-related time use activities (i.e. housework, childcare and paid work) and self-reported health among married men and women. Methods Data from the Multinational Time Use Study (MTUS) on 32,881 men and 26,915 women from Germany, Italy, Spain, the UK and the US were analyzed. Seemingly unrelated regression (SUR) models and multivariable logistic regression were used to estimate the association between role-related time use activities and self-reported health among married men and women. Results The findings showed that education, occupation and number of children under 18 years old in the household were the most consistent predictors of time allocation among married men and women. Significant gender differences were also found in time allocation, with women sacrificing paid working time or reducing time devoted to housework for childcare. Men, in contrast, were less likely to reduce paid working hours to increase time spent on childcare, but instead reduced time allocation to housework. Allocating more time to paid work and childcare was associated with good health, whereas time spent on housework was associated with poor health, especially among women. Conclusions Time allocation to role-related activities have differential associations on health, and the effects vary by gender and across countries. To reduce the gender health gap among married men and women, public policies need to take social and gender roles into account.